Space‐Based Observations for Understanding Changes in the Arctic‐Boreal Zone. (16th January 2020) - Duncan, Bryan N.; Ott, Lesley E.; Abshire, James B.; Brucker, Ludovic; Carroll, Mark L.; Carton, James; Comiso, Josefino C.; Dinnat, Emmanuel P.; Forbes, Bruce C.; Gonsamo, Alemu; Gregg, Watson W.; Hall, Dorothy K.; et al.
Abstract: Observations taken over the last few decades indicate that dramatic changes are occurring in the Arctic‐Boreal Zone (ABZ), which are having significant impacts on ABZ inhabitants, infrastructure, flora and fauna, and economies. While suitable for detecting overall change, the current capability is inadequate for systematic monitoring and for improving process‐based and large‐scale understanding of the integrated components of the ABZ, which includes the cryosphere, biosphere, hydrosphere, and atmosphere. Such knowledge will lead to improvements in Earth system models, enabling more accurate prediction of future changes and development of informed adaptation and mitigation strategies. In this article, we review the strengths and limitations of current space‐based observational capabilities for several important ABZ components and make recommendations for improving upon these current capabilities. We recommend an interdisciplinary and stepwise approach to develop a comprehensive ABZ Observing Network (ABZ‐ON), beginning with an initial focus on observing networks designed to gain process‐based understanding for individual ABZ components and systems that can then serve as the building blocks for a comprehensive ABZ‐ON. Plain Language Summary: While numerous scientific datasets of the Arctic Boreal Zone (ABZ) confirm that this region is rapidly changing, the current observational suite is insufficient to understand many of the complex interactions between components of the ABZ, which includes the cryosphere, biosphere, hydrosphere, and atmosphere. Such a process‐based understanding is necessary for the development of informed mitigation and adaptation response strategies and the prediction of future change. We review the strengths and limitations of the current suite of observations from satellites, which have the unique advantage of spatial coverage as compared to observations collected from near‐surface instruments. We make recommendations for improving satellite observations of individual components of the ABZ and recommend an interdisciplinary and stepwise approach to develop a comprehensive ABZ Observing Network (ABZ‐ON). Key Points: We review the strengths and limitations of space‐based observational capabilities for several important Arctic‐Boreal Zone components We make recommendations for improving the current Arctic‐Boreal Zone observing network and discuss how to build a more comprehensive one